Year-round monitoring of antibiotic-resistant bacteria in pristine uppermost stream and estimation of pollution sources - Nishimura, Emi; Xie, Hui; Tamai, Soichiro; Nishiyama, Masateru; Nukazawa, Kei; Hoshiko, Yuki; Ogura, Yoshitoshi; Suzuki, Yoshihiro (Frontiers in Environmental Science, 2024)
Studies on the conditions and pollution routes of antibiotic-resistant bacteria (ARB) in rivers can help provide countermeasures against the spread of ARB. This study focused on the pristine uppermost stream of a river, where Escherichia coli (E. coli) and enterococci were detected, although the stream flows through a pristine forest catchment. Antibiotic resistance of E. coli and enterococci isolated from the river water, riverbed sediment, and feces of waterside animals, such as birds and Mustelidae, were investigated throughout the year in the pristine uppermost sites. Antibiotic resistance was present in 1.4% (7/494) of the E. coli strains and 3.0% (24/812) of the enterococcal strains, and was low throughout the year. Although antibiotic resistance of bacteria isolated from feces was not detected in this watershed, the prevalence of multidrug-resistant E. coli was 0.4% (1/246) and 0.6% (1/172) in river water and riverbed sediment samples, respectively were observed. The presence of extended-spectrum β-lactamase (ESBL)-producing E. coli was confirmed in river water samples, and genomic analysis revealed that the samples possessed the CTX-M-15 group. Multidrug-resistant strains and ESBL-producing strains were classified as phylogroups B1 and A, respectively, which are E. coli phenotypes isolated from wild animals. Pulsed-field gel electrophoresis revealed analysis targeting enterococci that strains isolated from river water and bird feces were in the same cluster with 100% similarity. Therefore, bird feces are a source of enterococci in the uppermost stream of the river. Because multidrug-resistant bacteria and ESBL-producing bacteria were present in the pristine uppermost stream of the pristine river, urgent elucidation of the spreading routes of ARB is important.